Cross-linguistic interaction and cross-linguistic awareness: a cross tabulation - Letica Krevelj, Stela (Array, 2012)
The fact that multilingual users activate their previously acquired linguistic knowledge in L3 production has been widely acknowledged. However, the relationship between the level of activation of previously acquired languages and linguistic awareness in multilinguals calls for further research. The authors will present s study which examines the relationship between tacit and explicit cross-linguistic awareness in multilingual users during a lexical production task in L3. More specifically, the tacit cross-linguistic awareness was measured through the exploitation of affordances provided by the existence of either false or true cognates forms between previously acquired languages and L3 in the producation task, while the explicit cross-linguistic awareness was measured through the retrospective task in which participants were asked to report on the perceived distance between the three language and explain how they retrieved the lexical item in L3 production task. Participants in the study were 28 Croatian-Italian-English trilinguals, high-school students with comparable age of onset, degree of exposure and levels of proficiency in all three languages. The participants were given a paper and pencil test in which they were asked to read a list of sentences in English (their L3) and to supply a synonym for an underlined word in each sentence. The required synonymous words were slightly above the participants' level of knowledge and it was expected that they would activate their knowledge of previously acquired languages in the search for cross-linguistic equivalents.The synonyms were manipulated in terms of levels of formal and semantic similarity with the words in either L1 or L2. Upon completing the main task, the participants were administered a retrospective task. The purpose of the retrospective task was threefold: to gauge the level of explicit cross-linguistic awareness, participants' level of risk-taking in the main task, and additional tacit cross-linguistic awareness measured through a different, translation task. The findings should offer an additional insight into the relationship between cross-linguistic interaction and linguistic awareness, and the level of conscious cognitive control involved in the cross-language lexical search during the process L3 item retrieval.